The Batten disease gene Cln3 is required for the activation of intestinal stem cell during regeneration via JAK/STAT signaling in Drosophila - Yu, Zihua; Yan, Jinhua; Liu, Zhiming; Wang, Haiyan; Luo, Guanzheng; Chen, Haiyang (Frontiers in Cell and Developmental Biology, 2025)
CLN3 mutation causes Juvenile neuronal ceroid lipofuscinosis (JNCL, also known as Batten disease), an early onset neurodegenerative disorder. Patients who suffer from Batten disease often die at an early age. However, the mechanisms underlying how CLN3 loss develops Batten disease remain largely unclear. Here, using Drosophila midgut system, we demonstrate that Drosophila Cln3 has no effect on midgut homeostasis maintaince, including cellular component, intestinal stem cells (ISCs) proliferation and differentiation, but is necessary for ISC activation upon tissue damage. Cell type-specific Gal4 screening reveals that the failure of ISC activation during regeneration caused by Cln3 loss is ISC-autonomous. Through genetic analyses, we elucidate that JAK/STAT signaling in ISCs is not activated with Cln3 depletion upon tissue damage, and functions downstream of Cln3. Our study provides a potential mechanism underlying the development of CLN3-mediated Batten disease at cellular level.